Knowledge, attitude, and practice status of ovarian reserve function among women of childbearing age: a latent profile analysis - Wang, Yawen; Sun, Fei; Qin, Yue; Wang, Jue; Fu, Aiping; Yuan, Li; Lei, Xia; Zhou, Lin (Frontiers in Public Health, 2025)
ObjectivesWe aimed to explore the current status and latent profiles of knowledge, attitude, and practice (KAP) on ovarian reserve function among women of childbearing age and to identify the factors associated with these profiles.MethodsUsing convenience sampling, women of reproductive age in the Hangzhou area of China were enrolled as study participants between March and May 2025. Data were collected using a demographic questionnaire and an ovarian reserve KAP instrument. A latent profile analysis was conducted on the ovarian reserve function KAP, and a multivariate logistic regression analysis was used to explore the influencing factors of different profiles.ResultsA total of 333 women of reproductive age were included in the study. The ovarian reserve function KAP score was 55.00 ± 7.06 points, the knowledge dimension score was 9.23 ± 1.59 points, the attitude dimension score was 27.58 ± 3.74 points, and the practice dimension score was 18.19 ± 2.93 points. The data were divided into three latent profiles: high knowledge-high attitude-high practice type (39.04%), high knowledge-moderate attitude-moderate practice type (38.74%), and low knowledge-low attitude-low practice type (22.22%). Multivariate analysis identified age, occupation, and production history were factors influencing the different latent profiles of the ovarian reserve function KAP.ConclusionThe KAP on ovarian reserve function among women of childbearing age is at an intermediate level and exhibits significant variability across different groups. Relevant educators and healthcare professionals should develop personalized intervention plans tailored to the specific characteristics and influencing factors of each group to enhance overall KAP, thereby safeguarding reproductive health.